Kemampuan Berpikir Komputasi dan Motivasi Belajar Matematika Siswa SMA Berdasarkan IQ - Mustafa, Mustafa; Azis, Azis (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
Based on previous research, Computational Thinking (CT) skills and learning motivation can be influenced by differences in IQ. Furthermore, learning motivation is correlated with and has an impact on CT skills. However, studies on CT skills, learning motivation, and IQ in mathematics, as well as the relationship between CT skills in mathematics and learning motivation, are still limited. Therefore, this research was conducted to address this gap. This study employed a descriptive quantitative method with a comparative and correlational design. The participants in this study were students from a high school in Medan, with a total of 41 subjects. Data were collected using a mathematical problem-solving test to measure CT skills and a questionnaire to assess students' learning motivation. The data were analyzed using simple and multivariate linear regression. The findings of the study is CT skills of students in the IQ group ≥ 100 were better than those in the IQ group < 100 in solving mathematical problems. There was no significant difference in learning motivation between students in the IQ group ≥ 100 and those in the IQ group < 100. There is a significant relationship and influence of learning motivation on CT skills.